M$1'Xu(Bsbauer spectroscopy :s applications in chemistry, biology, industry, and nanotechnology - Sharma, Virender K.; Klingelhofer, Gostar, 1956-; Nishida, Tetsuaki, 1950- (Hoboken, New Jersey : Wiley, 2014)
'A one-stop reference for determining the oxidation states of elements so that oxidation eduction chemistry can be studied across a wide variety of systems, this book presents advances in the field from the last two decades. Beginning with a detailed theoretical description of Mossbauer spectroscopy, followed by an extensive treatment of its use in applied areas such as synchrotron radiation, biotechnology, and nanoparticle analysis, the book discusses future opportunities for the further development of this technique. Designed for spectroscopists, inorganic, physical, analytical, and solid-state chemists and other researchers'--
'This book serves as a one-stop reference for the characterization of metal and other elements in solid materials. Presenting advances gained on Mossbauer Spectroscopy in the last two decades, it begins with a detailed theoretical description of Mossbauer spectroscopy'--
Includes bibliographical references and index.
Keywords: Mossbauer spectroscopy